Fatty Acid Amide Hydrolases: An Expanded Capacity for Chemical Communication?. (March 2020) - Aziz, Mina; Chapman, Kent D.
Abstract : Fatty acid amide hydrolase (FAAH) is an enzyme that belongs to the amidase signature (AS) superfamily and is widely distributed in multicellular eukaryotes. FAAH hydrolyzes lipid signaling molecules – namely, N -acylethanolamines (NAEs) – which terminates their actions. Recently, the crystal structure of Arabidopsis thaliana FAAH was solved and key residues were identified for substrate-specific interactions. Here, focusing on residues surrounding the substrate-binding pocket, a comprehensive analysis of FAAH sequences from angiosperms reveals a distinctly different family of FAAH-like enzymes. We hypothesize that FAAH, in addition to its role in seedling development, also acts in an N -acyl amide communication axis to facilitate plant–microbe interactions and that structural diversity provides for the flexible use of a wide range of small lipophilic signaling molecules. Highlights: Fatty acid amide hydrolase (FAAH) is the signal-terminating enzyme of the N -acylethanolamine signaling pathway with an established role in seedling development. The crystal structure of Arabidopsis thaliana FAAH was recently solved, revealing for the first time the structural features of FAAH from plants and explaining the enzyme's promiscuity toward N -acyl amide substrates. A second group of FAAH enzymes in angiosperms has been identified with conserved substitutions in the substrate-binding pocket altering the size, shape, and physicochemical properties for substrate recognition.